An analysis of Delta Air Lines' oil refinery acquisition. (August 2016) - Manuela Jr., Wilfred S.; Rhoades, Dawna L.; Curtis, Tamilla
Abstract: Delta Air Lines acquired an oil refinery in April 2012 as a strategic move to hedge against higher fuel prices. Our paper analyzes the impact of the oil refinery acquisition, a backward integration strategy, on the airline's financial and operational performance, for the period Q1 2010 to Q2 2015, and we argue that the resource dependence theory best explains Delta Air Lines' acquisition. The methodology involves descriptive statistics and short-term stock performance as well as an econometric model that estimates the impact of the oil refinery acquisition on Delta Air Lines' net income using quarterly financial and airline operating metrics data. The results indicate that it is too early to ascertain whether Delta Air Lines' oil refinery acquisition has any positive impact on its financial performance since the variable of interest is insignificant in predicting the airline's net income. Despite the apparent lack of positive impact of its oil refinery acquisition, however, the stock market has rewarded Delta Air Lines' strategy resulting in its share prices outperforming the S&P 500 and the XAL, an index of major airline stocks, in the 60-trading day period following the announcement of its acquisition.